“Disorganised Devolution”: Reshaping Metropolitan Governance in England in a Period of Austerity - Shaw, Keith; Tewdwr-Jones, Mark (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
After 2010, the UK Government’s espousal of a Localist agenda reflected a rejection of the regional level as the most appropriate scale for sub-national governance. The development of a more explicitly city regional level of governance is illustrated in the creation of City Deals which have given some of England’s largest cities increased autonomy to allocate the dividend of local economic growth. More recently, Combined Authorities have been formed, within which larger city-regions such as Manchester, Sheffield, Leeds, Liverpool and the North-East of England have been tasked to undertake transport, economic development and other functions. In assessing this contemporary reshaping of metropolitan governance this article draws upon political economy, spatial and institutional approaches that highlight how austerity, competing spatial imaginaries and the historical evolution of central-local relationships within the UK state have combined to produce a particularly ‘disorganised’ approach to contemporary devolution in England. It contends that while the city region remains the dominant spatial narrative, the on-going process of rescaling at the sub-national state level falls well short of being a coherent, clearly thought-out and permanent transfer of powers and fiscal responsibilities to a uniformly defined scale of governance.
Keywords: Devolution; Governance; Region; City; Economy